(untitled) (World Economics and Finance Bulletin, 2023)
This article provides a thorough exploration of bank liabilities, dissecting the various components that constitute the financial obligations of financial institutions. Through an in-depth analysis, the article aims to shed light on the intricacies of bank liabilities, their implications on financial health, and the broader implications for the banking sector.